Psychosocial risk among migrant workers: what we can learn from literature and field experiences / Rischio psicosociale nei lavoratori immigrati: cosa si apprende dalla letteratura e da esperienze sul campo - Porru, Stefano; Elmetti, S.; Arici, Cecilia (La Medicina del Lavoro, 2014)
SUMMARY Background: Mental health problems are possible in migrant workers (MWs), who are mainly employed in dangerous jobs and face many barriers to prevention and care. Objectives: To outline current scientific evidence about psychosocial risk among MWs; to present data from clinical and field experiences. Methods: Nonsystematic literature review (PubMed, last 10 years); case series of 20 MWs, evaluated for mental and/or behavioural disorders at a public occupational health unit; applied field research, in enterprise contexts. Results: A relatively low number of publications about psychosocial risk among MWs was found. Individual migrants may find the experience of migration to be stressful, with increased rates of depression and/or anxiety disorders. Data from clinical case series suggest that MWs from some ethnic groups, with a mediumhigh level of education, employed in metal or manufacturing industries, might have an increased risk of developing psychiatric disorders. Preliminary data from our field study seem to confirm that MWs, predominantly employed in unskilled/manual jobs and more prone to work overtime, tend to present higher prevalence of psychiatric disorders. Conclusions: There is a growing need to improve the scientific knowledge on migration, work, and mental health, as well as to promote workplace prevention of mental disorders in MWs. This can be achieved also by reducing structural barriers to mental wellbeing: in particular, occupational physicians should answer to MWs’ mental health needs, contributing both to diagnosis and management of MWs’ workrelated psychiatric disorders. RIASSUNTO «Rischio psicosociale nei lavoratori immigrati: cosa si apprende dalla letteratura e da esperienze sul campo». Introduzione: Problemi di salute mentale sono possibili in lavoratori migranti (LM), che sono impiegati nei lavori rischiosi e affrontano ostacoli alla prevenzione e cura. Obiettivi: Delineare le evidenze scientifiche attuali sul rischio psicosociale nei LM; presentare dati da esperienze cliniche e sul campo. Metodi: Revisione non sistematica di letteratura (PubMed, ultimi 10 anni); casistica di 20 LM, valutati per disturbi mentali e/o comportamentali presso unità operativa ospedaliera pubblica di medicina del lavoro; ricerca applicata in aziende, sul campo. Risultati: È stato reperito un numero relativamente basso di pubblicazioni sul rischio psicosociale nei LM. Singoli LM possono trovare stressante l’esperienza della migrazione,con un incremento di depressione e/o disturbi d’ansia. Dati rilevati dai casi clinicamente valutati suggeriscono che i LM provenienti da alcune etnie, con livello d’istruzione medioalto, impiegati nell’industria dei metalli o manifatturiera presentano aumentato rischio di sviluppare disturbi psichiatrici. Dati preliminari dallo studio sul campo indicano che i LM, prevalentemente impiegati in lavori non qualificati/manuali e più inclini a svolgere lavoro straordinario, tendono a presentare una maggiore prevalenza di disturbi psichiatrici. Conclusioni: Vi è una crescente necessità di miglioramento della conoscenza scientifica sul tema migrazione, lavoro e salute mentale, nonché di promuovere la prevenzione dei disturbi psichiatrici in LM nei luoghi di lavoro. Ciò potrà avvenire anche mediante la riduzione delle barriere strutturali al benessere mentale; in particolare, i medici del lavoro dovrebbero rispondere concretamente ai bisogni di salute mentale dei LM, concorrendo sia alla diagnosi dei disturbi psichiatrici lavorocorrelati nei LM che alla loro gestione.